“Asfixia dewl recien nacido: Factores predisponentes en el hospital II IPSS Tarapoto, periodo Agosto 1994 Julio 1995” - Velásquez Campoverde, Mirta Arazela (1995)
This paper stresses the importance of the asphyxia of the newborn as a serious event that increases morbidity rates in this age group. Becomes the study of the main factors predispose teas, both maternal, obstetric and the inherent to the or ~ or that may play some role in the presentation of the asphyxia of the newborn, in 1038 births occurring in the services of obstetrics and gynaecology Hospital II IPSS Tarapoto, since the month of August 1994 until the month of July 1995; of which 49 newborns presented some degree of suffocation, which is worked with 2 groups, an experimental group constituted by the 49 neonates with asphyxia, and a control group consisting of a similar number of newly born with optimal Apgar (7-10). The analysis of the casuistry in reference was obtained the following important conclusions: frequency of suffocation 4.7 per cent factors as the absence of prenatal care ~ age matern...